John Glendy Sproston journal - Sproston, John Glendy, 1828-1862.
Journal (1854 February-August) kept by Sproston as a member of the U.S. naval expedition to Japan led by Commodore Matthew Calbraith Perry.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Perry, Matthew Calbraith, -- 1794-1858.; Japan -- Description and travel; Japan -- Foreign relations -- United States; United States -- Foreign relations -- Japan; Midshipmen